Decoding fMRI alcohol cue reactivity and its association with drinking behaviour - Tan, Haoye; Gerchen, Martin Fungisai; Bach, Patrick; Lee, Alycia; Hummel, Oliver; Sommer, Wolfgang H.; Kirsch, Peter; Kiefer, Falk; Vollstädt-Klein, Sabine (BMJ mental health, 2023)
Background Cue reactivity, the enhanced sensitivity to conditioned cues, is associated with habitual and compulsive alcohol consumption. However, most previous studies in alcohol use disorder (AUD) compared brain activity between alcohol and neutral conditions, solely as cue-triggered neural reactivity. - Objective This study aims to find the neural subprocesses during the processing of visual alcohol cues in AUD individuals, and how these neural patterns are predictive for relapse. - Methods Using cue reactivity and rating tasks, we separately modelled the patterns decoding the processes of visual object recognition and reward appraisal of alcohol cues with representational similarity analysis, and compared the decoding involvements (ie, distance between neural responses and hypothesised decoding models) between AUD and healthy individuals. We further explored connectivity between the identified neural systems and the whole brain and predicted relapse within 6 months using decoding involvements of the neural patterns. - Findings AUD individuals, compared with healthy individuals, showed higher involvement of motor-related brain regions in decoding visual features, and their reward, habit and executive networks were more engaged in appraising reward values. Connectivity analyses showed the involved neural systems were widely connected with higher cognitive networks during alcohol cue processing in AUD individuals, and decoding involvements of frontal eye fields and dorsolateral prefrontal cortex could contribute to relapse prediction. - Conclusions These findings provide insight into how AUD individuals differently decode alcohol cues compared with healthy participants, from the componential processes of visual object recognition and reward appraisal. - Clinical implications The identified patterns are suggested as biomarkers and potential therapeutic targets in AUD.